Acquired Megacolon in adults.: Duhamel - Haddad technique - Farcic, Antonio; Viola Núñez, Humberto; Delgado, Bolívar; Aguiar, Alberto; Soto Carriquiry, Juan P (Cirugía del Uruguay, 1980)
Report on the treatment of four adult patients with megacolon by Duhamel - Haddad's technique. There is a description of technique employed, case material and evolution of surgical treatment. Results are analyzed on the basis of morbimortality and compared with those from other techniques used. A revision of the numerous series which appear in national' and foreign literature indicate that results with this technique are superior.